2022
DOI: 10.1007/s40123-022-00492-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiseptics and the Ocular Surface: In Vitro Antimicrobial Activity and Effects on Conjunctival and Corneal Epithelial Cells of a New Liposomal Ocular Spray Containing Biosecur® Citrus Extract

Abstract: Introduction:The study aimed to evaluate the in vitro antimicrobial activity of a new liposomal ocular spray containing the antiseptic Biosecur Ò citrus extract (Oftasecur, OFF-HEALTH, Florence, Italy) and its in vitro effects on cultured human corneal and conjunctival cells. Methods: Minimal inhibitory concentrations (MIC) and minimal bactericidal concentrations (MBC) of Oftasecur against Candida albicans and Gram-positive and Gram-negative bacteria, including antibiotic-resistant strains, were determined. Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In contrast, 10.1 µL of Oftasecur was required to impair bacterial growth. Consistent with our results, a preliminary study conducted by Mencucci and colleagues reported the antimicrobial effect of Oftasecur against S. aureus , S. epidermidis , S. pyogenes , E. coli , P. aeruginosa, and C. albicans , recording a bactericidal effect and fungicide against the microorganisms analyzed [ 33 ]. Otherwise, no studies to date have investigated the antimicrobial effect of Visuprime.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, 10.1 µL of Oftasecur was required to impair bacterial growth. Consistent with our results, a preliminary study conducted by Mencucci and colleagues reported the antimicrobial effect of Oftasecur against S. aureus , S. epidermidis , S. pyogenes , E. coli , P. aeruginosa, and C. albicans , recording a bactericidal effect and fungicide against the microorganisms analyzed [ 33 ]. Otherwise, no studies to date have investigated the antimicrobial effect of Visuprime.…”
Section: Discussionsupporting
confidence: 91%
“…Both ophthalmic solutions were commercially available to soothe and protect the surface of the eye. In the ophthalmology field, antiseptics are becoming a relevant therapeutic approach due to their broad-spectrum activity for nonselective mechanisms of action [ 33 , 34 ]. Little evidence reports the antimicrobial potential of Visuprime and Oftasecur.…”
Section: Discussionmentioning
confidence: 99%
“…Biosecur is a non-toxic organic alcohol-free compound containing citrus bioflavonoids suspended in glycerin. Mencucci et al tested in vitro a liposomal commercial formulation, Oftasecur Ocular Spray (OFFHEALTH S.p.a., Florence, Italy) containing 0.2% biosecur, reporting bactericidal and fungicidal effects versus all common microorganisms at dilutions varying from 1:2 to 1:16 [73]. Moreover, Vagge et al tested the compound in vivo in a prospective study on patients undergoing IVIs, reporting a significant decrease in conjunctival bacterial load after a 4-day prophylactic treatment [74] (Fig.…”
Section: Biosecurmentioning
confidence: 99%
“…These studies focused on its use as surface cleaner or supported its application as food treatment in the food industry. The citrus extract is also included as active ingredient in a liposomal formulation commercialized as medical device for the ocular antisepsis ( Vagge et al, 2021 ; Mencucci et al, 2022 ; Mazzantini et al, 2024 ). Nevertheless, evidence on the potential application of B in the clinical practice to treat staphylococcal infections is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Time-kill assay was carried out using S. aureus ATCC 6538 and S. epidermidis CI-1 as model organisms, as previously described ( Mencucci et al, 2022 ). Briefly, microbes were suspended in 0.01 M Sodium Phosphate Buffer (NaPB, pH 7.2) to a density of 0.5 McF and about 10 6 CFU inoculated in NaPB containing the extract at the MIC value (0.0031% for S. aureus ATCC 6538 and 0.0063% for S. epidermidis CI-1).…”
Section: Methodsmentioning
confidence: 99%